The Effect of Using YouTube Animation Learning Media in Improving Gross Motor Skills in Early Age Children 4-5 Years at Ar-Rahim 1 Kindergarten, Simpang Tiga Village, North Kaur District, Kaur Regency - Diana, Novitasi; Nirwana, Evi Selva (International Journal of Education, Information Technology, and Others, 2024)
Early childhood is a critical period of rapid growth and development, during which children can easily capture adult cues. In early childhood education, children aged 0-8 years are classified as young children, each with unique potential that requires a supportive environment to maximize. Among the six domains of development highlighted in early childhood education standards are physical motor skills, which include both fine and gross motor skills. These skills are foundational and should be carefully cultivated as they relate to the child’s overall physical and behavioral development. In early childhood education settings, physical motor development is particularly important, with fine motor skills involving small muscle coordination and gross motor skills involving larger muscle movements. Developing motor skills through engaging activities, such as games, physical exercises, and multimedia resources, helps children gain coordination, strength, and balance. Animated video learning media is a promising tool for stimulating motor skill development as it captures children’s attention and motivates them to move. Previous research indicates that interactive media, including animations, can enhance children’s motor coordination and overall engagement in physical activities. This study, conducted at TK Ar-Rahim 1, Simpang Tiga, Kaur Utara, explores the influence of animated video learning media on the gross motor skill development of early childhood students. Initial observations revealed limited use of engaging learning media due to constraints in resources and teacher creativity. Through analyzing the effects of animated video media on motor skills, this research seeks to provide insights into its potential benefits and to contribute to early childhood education practices that support optimal motor development.